Coronary Artery Bypass Grafting in Diabetic Patients: Complete Arterial versus Internal Thoracic Artery and Sequential Vein Grafts—A Propensity-Score Matched Analysis - Kunihara, Takashi; Wendler, Olaf; Heinrich, Kerstin; Nomura, Ryota; Schäfers, Hans-Joachim (The Thoracic and Cardiovascular Surgeon, 2019)
Background The optimal choice of conduit and configuration for coronary artery bypass grafting (CABG) in diabetic patients remains somewhat controversial, even though arterial grafts have been proposed as superior. We attempted to clarify the role of complete arterial revascularization using the left internal thoracic artery (LITA) and the radial artery (RA) alone in “T-Graft” configuration on long-term outcome.Methods and Results From 1994 to 2001, 104 diabetic patients with triple vessel disease underwent CABG using LITA/RA “T-Grafts” (Group-A). Using propensity-score matching, 104 patients with comparable preoperative characteristics who underwent CABG using LITA and one sequential vein graft were identified (Group-V). Freedom from all causes of death, cardiac death, major adverse cardiac event (MACE), major adverse cardiac (and cerebral) event (MACCE), and repeat revascularization at 10 years of Group-A was 60 ± 5%, 67 ± 5%, 48 ± 5%, 37 ± 5%, and 81 ± 4%, respectively, compared with 58 ± 5%, 70 ± 5%, 49 ± 5%, 39 ± 5%, and 93 ± 3% in Group-V. There were no significant differences in these end points between groups regardless of insulin-dependency. Multivariable Cox proportional hazards model identified age, left ventricular ejection fraction, renal failure, and hyperlipidemia as independent predictors for all death, age and left ventricular ejection fraction for cardiac death, sinus rhythm for both MACE and MACCE, and prior percutaneous coronary intervention for re-revascularization.Conclusions In our experience, complete arterial revascularization using LITA/RA “T-Grafts” does not provide superior long-term clinical benefits for diabetic patients compared with a combination of LITA and sequential vein graft.
Keywords: CABG; arterial revascularization; internal thoracic artery; radial artery; diabetes mellitus